2017
DOI: 10.1159/000478764
|View full text |Cite
|
Sign up to set email alerts
|

RU486 Reverses Emotional Disorders by Influencing Astrocytes and Endoplasmic Reticulum Stress in Chronic Restraint Stress Challenged Rats

Abstract: Aims: To investigate the effect of RU486 (mifepristone) on emotional disorders in chronic restraint stress-induced rats and to explore the mechanisms of that phenomenon. Methods: For this purpose, 80 healthy male Sprague Dawley rats were randomly divided into four groups: the normal group (Con group, The Con group members received no treatment, eating and drinking freely), the chronic restraint stress group (CRS group, normal Sprague Dawley rats treated with chronic restraint stress, 6 h/day for 21days), the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…In the EPM test, the CRS þ Sham group which exposed to CRS procedure was less tended to enter and spent time in the open arms and both %OAE and %OAT parameters significantly declined compared to the control group. These results are parallel to the prior depression studies [27,28]. In a study by Salehpour et al [20] the anti-anxiety effect of NIR (810 nm, 10 Hz) TPBM in CMS rat was evaluated by EPM test.…”
Section: Discussionsupporting
confidence: 78%
“…In the EPM test, the CRS þ Sham group which exposed to CRS procedure was less tended to enter and spent time in the open arms and both %OAE and %OAT parameters significantly declined compared to the control group. These results are parallel to the prior depression studies [27,28]. In a study by Salehpour et al [20] the anti-anxiety effect of NIR (810 nm, 10 Hz) TPBM in CMS rat was evaluated by EPM test.…”
Section: Discussionsupporting
confidence: 78%
“…At the used dose and injection volume, mifepristone is characterized by poor solubility in aqueous vehicles. To improve the solubility, 100% propylene glycol [45] was slowly added to the compound while mixing with a magnetic stir bar. The 60 mg/kg dose and 90 min pretreatment were chosen based on previously published reports demonstrating that the acute systemic administration of this dose of mifepristone reduces alcohol reinforcement [21], and doses ranging between 20 mg/kg and 120 mg/kg have an anxiolytic effect in male rats [35,36].…”
Section: Drug Preparation and Treatmentmentioning
confidence: 99%
“…Several studies have revealed restraint stress could induce atrophy of glutamatergic pyramidal neurons in the amygdala, potentially leading to mental disorders (Padival et al, 2013; Grillo et al, 2015). Our previous study has also suggested restraint stress to be linked with degeneration of amygdalar neurons and astrocytes in rats and induce behavioral changes, such as anxiety and depression (Dong et al, 2017). Nevertheless, the specific mechanisms underlying these phenomena remain unclear.…”
Section: Introductionmentioning
confidence: 99%